2017
DOI: 10.1021/acs.macromol.7b01117
|View full text |Cite
|
Sign up to set email alerts
|

Wavelength-Selective Sequential Polymer Network Formation Controlled with a Two-Color Responsive Initiation System

Abstract: We report a wavelength-selective polymerization process controlled by visible/UV light, whereby a base is generated for anion-mediated thiol–Michael polymerization reaction upon exposure at one wavelength (400–500 nm), while radicals are subsequently generated for a second stage radical polymerization at a second, independent wavelength (365 nm). Dual wavelength, light controlled sequential polymerization not only provides a relatively soft intermediate polymer that facilitates optimum processing and modificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
66
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 48 publications
0
66
0
Order By: Relevance
“…With its unique properties, light can serve as a gate to control chemical bond formation and cleavage, which in turn permits precise control over both chemical and physical properties of materials 8–10. In the field of hydrogels, a number of studies have successfully developed light‐based methods to tune the mechanical properties of gels for their subsequent utilization in biomaterial engineering 11–14…”
Section: Introductionmentioning
confidence: 99%
“…With its unique properties, light can serve as a gate to control chemical bond formation and cleavage, which in turn permits precise control over both chemical and physical properties of materials 8–10. In the field of hydrogels, a number of studies have successfully developed light‐based methods to tune the mechanical properties of gels for their subsequent utilization in biomaterial engineering 11–14…”
Section: Introductionmentioning
confidence: 99%
“…[6,9] Photochemistry offers unique spatiotemporal control over the gelation process,a llowing customizable patterning [10] and the precise tuning of the degree of crosslinking. [11] Approaches reported for light-induced network formation encompass photoinduced thiol chemistry, [11][12][13][14] photodimerization reactions, [15] photoinitiated radical and cationic polymerization, [16,17] and photoactivated cycloaddition reactions. [6] Among these strat-egies,t he nitrile imine mediated tetrazole-ene cycloaddition (NITEC), aUV-induced reaction that generates afluorescent five-membered pyrazoline ring, [18] was applied to crosslink polymer chains,y ielding intrinsically fluorescent gels.…”
mentioning
confidence: 99%
“…[22] Rheological measurements, swelling ratios,gravimetry,calorimetry,and thermal analyses are employed to analyze the bulk properties of gels.T he detailed characterization of networks including the number of crosslinks and structural defects is still challenging.T he high complexity of crosslinked systems hampers their quantitative structural analysis by common solid-state spectroscopic techniques.O ne useful spectroscopic method to monitor network formation is FTIR spectroscopy,s ince kinetic information can be obtained by following changes in transmittance of specific IR bands. [11,12,17] Acquisition of quantitative data by IR spectroscopy often requires very careful sample preparation and ah igh local concentration of the functional groups.A na lternative approach is the use of degradable gels,which can be disassembled chemically [11,23,24] or photochemically, [9,10,25] permitting their analysis by solution-based spectroscopy.F or example,J ohnson and colleagues designed an elegant site-selective network-disassembly system, [23][24][25] allowing the quantification of structural defects present in the original gels by the analysis of obtained degradation fragments.…”
mentioning
confidence: 99%
“…In contrast to the thermal reactions described by Hayashi and Studer, we have found that the synthesis of n‐type CPs requires photochemical conditions. Photopolymerizations offer the opportunity for spatiotemporal control and selective catalyst activation by different wavelengths of light . For non‐conjugated polymers, researchers have developed a range of photocontrolled polymerizations .…”
Section: Introductionmentioning
confidence: 99%
“…conditions.P hotopolymerizations offer the opportunity for spatiotemporal control [16][17][18] and selective catalyst activation by different wavelengths of light. [19][20][21] Forn on-conjugated polymers,r esearchers have developed ar ange of photocontrolled polymerizations. [22][23][24][25] To date,there have been few examples of photopolymerizations to produce CPs.…”
mentioning
confidence: 99%